Exploring physical education teachers’ perspectives on modern vs. traditional teaching approaches and practices - Aliaj, Blerina; Cenaj, Mirjeta; Ushtelenca, Keida,; Ҫaushi Alketa (Edelweiss Applied Science and Technology, 2025)
Teaching is a multifaceted process that depends on both the methods employed and how effectively teachers implement and deliver them. This study aims to assess the usage of modern techniques and methods consistently applied by Physical Education teachers in Albania. It intends to identify the most frequently utilized approaches in PE classes and determine which methods are the most effective. In order to carry out this study, a combination of quantitative (surveys) and qualitative (interviews, discussions) approaches was employed. Modern approaches are utilized in our educational institutions, but educators, particularly those with extensive experience, often remain traditional in their teaching methods. At the same time, newly qualified teachers require additional training, informal conversations, and open workshops within their departments. This study validates the hypothesis that contemporary teaching methods significantly enhance the quality and effectiveness of primary education. It is concluded that modern teaching techniques lead to significant transformations in the educational process due to teachers’ attempts to adopt learner-centered teaching models, which are crucial for contemporary and high-quality education. These results reinforce the positive relationship between modern teaching practices and the quality of education, confirming the original hypothesis.